Perancangan Sistem Smart Office Berbasis Internet of Things Politeknik Penerbangan Makassar - Agung Raharjo, Muhammad; Sabur, Fatmawati (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2020)
The problem that raised in this research is how to solve problems in using office electronic equipment to make it more efficient by utilizing internet technology as a medium for controlling, air conditioning, computers, and lights. Sometimes we still find a room that has electronic equipment such as air conditioning, computers, and lights that are still on even though they are not used so that it seems wasteful and inefficient, therefore we need an Internet of Things-based smart office system that can regulate and control conditions. office electronic equipment from anywhere via the internet network so that it can be useful for identifying and monitoring whether it is on or off. The control system is expected to help to identify and monitor the switching on and off of electronic devices remotely through a user interface. This research aims to design a smart office system based on the internet of things so that it can be used to flexibly identify and control office electronic equipment. The results of this study resulted in a prototype of a smart office system based on the internet of things that can help identify and control electronic equipment in the office